The prevalence of patellofemoral pain in the Rugby League World Cup (RLWC) 2021 spectators: A protocol of a cross-sectional study. - María B Sánchez; James Selfe; Michael J Callaghan (PLoS ONE, 2021)
Patellofemoral pain (PFP) can cause significant pain leading to limitations in societal participation and physical activity. PFP is usually associated with athletes undergoing intensive physical training, or military recruits; but recent evidence shows that PFP is common in the general population. The relationship of PFP with physical activity is not entirely clear. Our aim is to provide a better estimate of the general population prevalence of PFP and to relate this to the level of physical activity, and demographic characteristics. The Survey instrument for Natural history, Aetiology and Prevalence of Patellofemoral pain Studies (SNAPPS) was developed as a PFP screening tool to be used in the community. The electronic version of the SNAPPS (eSNAPPS) has recently been validated and was used to survey attendees at mass-participation running events. We will use an electronic survey to collect data from a sample of 1100 Rugby League World Cup spectators. The survey will have four sections: i) general and demographic; ii) knee pain (eSNAPPS); iii) level of physical activity; and iv) quality of life in relation to knee pain. The primary analytic approach will be descriptive of PFP prevalence. Secondary analyses will explore the relationships of the presence of PFP and the other variables. We will disseminate this work by publication of peer-reviewed papers in scientific journals, presentations at scientific conferences, and on the dedicated SNAPPS website https://www.snappspfp.com/.